Improved control of exogenous attention in action video game players - Cain, Matthew S.; Prinzmetal, William; Shimamura, Arthur P.; Landau, Ayelet N. (Frontiers in Psychology, 2014)
Action video game players have demonstrated a number of attentional advantages over non-players. Here, we propose that many of those benefits might be underpinned by improved control over exogenous (i.e., stimulus-driven) attention. To test this we used an anti-cuing task, in which a sudden-onset cue indicated that the target would likely appear in a separate location on the opposite side of the fixation point. When the time between the cue onset and the target onset was short (40 ms), non-players (nVGPs) showed a typical exogenous attention effect. Their response times were faster to targets presented at the cued (but less probable) location compared with the opposite (more probable) location. Video game players (VGPs), however, were less likely to have their attention drawn to the location of the cue. When the onset asynchrony was long (600 ms), VGPs and nVGPs were equally able to endogenously shift their attention to the likely (opposite) target location. In order to rule out processing-speed differences as an explanation for this result, we also tested VGPs and nVGPs on an attentional blink task. In a version of the attentional blink task that minimized demands on task switching and iconic memory, VGPs and nVGPs did not differ in second target identification performance (i.e., VGPs had the same magnitude of attentional blink as nVGPs), suggesting that the anti-cuing results were due to flexible control over exogenous attention rather than to more general speed-of-processing differences.